Revisiting writing feedback: Using teacher-student writing conferences to enhance learners’ L2 writing skills - Kumneger Chenekew Goshu; Hailay Tesfay Gebremariam (Ampersand)
Previous studies have largely overlooked teacher feedback, which plays a significant role in the social construction of knowledge within educational ecosystems worldwide. While written corrective feedback has been the focus of writing feedback research, oral feedback in teacher-student L2 writing conferences has not received as much attention, especially from an ecological lens. To address this research gap, this study investigated how writing training, including teacher-student conferences, can improve learners' L2 writing skills, with a specific focus on Ethiopia. The study explores how these conferences can help students enhance their L2 writing skills through constructive criticism and encouragement. To achieve this, 63 students (aged 15 to 23; 38 male and 25 female) were divided into experimental and control groups using a quasi-experimental design. The students underwent pre- and post-tests during an eight-week intervention. MANOVA was used to evaluate the pre-test data, while ANCOVA was used for the post-test analysis. The post-test results show that teacher-student conferences can effectively improve three writing skills: organization, vocabulary, and mechanics. The greatest impact on students' understanding of the writing process was seen in mechanics (43.4%), vocabulary (36.9%), and organization (11.5%). However, the intervention did not have a statistically significant impact on two other writing skills: content and language usage or grammar. Recommendations for future research and strategies for integrating teacher-student conferences into writing instruction are provided.